High-accuracy emission modeling of yellow phosphor YAG: Ce validated by normalized cross-correlation - Nguyen , Huynh-Tuan-Anh; Huynh, Van-Tuan; Nguyen , Quoc-Cuong; Nguyen, Quang-Khoi (Photonics Letters of Poland, 2024)
The emission of yellow phosphor YAG:Ce3+ shows an asymmetric shape that causes the difficulty of spectrum modeling. We proposed and demonstrated a method for modeling the emission of yellow phosphor YAG:Ce3+. The mathematical model is developed based on the Gaussian function. The model's accuracy is quantitatively verified by comparing the simulation and experimental results. Normalized cross-correlation algorithms were applied to quantitatively define the similar level between the simulation and experiment results. The proposed model is helpful for emission spectrum modeling and efficient for studying the optical properties of yellow phosphor. Full Text: PDF References E.F. Schubert, J.-K. Kim, "Solid-state light sources getting smart", Science, 308, 1274 (2005). CrossRef E. Schubert, Light-Emitting Diodes (2nd ed.). Cambridge: Cambridge University Press (2006). CrossRef P. Singh, C.-M. Tan, "Degradation Physics of High-Power LEDs in Outdoor Environment and the Role of Phosphor in the degradation process", Sci. Rep., 6, 24052 (2016). CrossRef J.-L. Davis, K.-C. Mills, G. Bobashev, K.-J. Rountree, M. Lamvik, R. Yaga, C. Johnson, "Understanding chromaticity shifts in LED devices through analytical models", Microelectron. Reliab., 84, 149 (2018). CrossRef Q.-K. Nguyen, T.-P.-L. Nguyen, V.-T.-T Huynh, N.-T. Phan, H.-T.-A. Nguyen, "An efficient decay model for studying the luminous flux behavior of phosphor-converted white light-emitting diodes", Photonics Lett. Pol.,15(4), 72 (2023). CrossRef C.-C. Sun , Y.-N. Peng, Y.-Y. Chang, H.-X. Chen, T.-X. Lee,"Re-Absorption Effect Modeling for Dual-Layer Phosphor Package of White LEDs", IEEE Phot. J., 13(4), (2021). CrossRef T.-H. Yang, C.-Y. Chen, Y.-Y. Chang, B. Glorieux, Y.-N. Peng, H.-X. Chen, T.-Y. Chung, T.-X. Lee, C.-C. Sun, "Precise Simulation of Spectrum for Green Emitting Phosphors Pumped by a Blue LED Die," IEEE Photonics Journal, 6(4), 1 (2014). CrossRef C.-C. Sun, T.-X. Lee, S.-H. Ma, Y.-L. Lee, S.-M. Huang, "Precise optical modeling for LED lighting verified by cross correlation in the midfield region" Opt. Lett. 31(14), 2193 (2006). CrossRef W.-T. Chien, C.-C. Sun, I. Moreno, "Precise optical model of multi-chip white LEDs, Opt. Expr. 15(12), 7572 (2007). CrossRef C.-C. Sun, Y.-Y. Chang, Y.-H. Wang, C.-Y. Chen, Y.-C. Lo, H.-H. Cheng, "Optical Modeling with Precise Spatial-chromatic Light Distribution in Phosphor-converted White LEDs", Proc. SPIE 9578, Current Developments in Lens Design and Optical Engineering XVI, 95780V (3 September 2015). CrossRef T.-H. Yang, H.-Y. Huang, C.-C. Sun, et al. "Noncontact and instant detection of phosphor temperature in phosphor-converted white LEDs", Sci. Rep. 8, 296 (2018). CrossRef Q.-K. Nguyen, "Emission spectrum modeling of white LEDs light source with using Gaussian function", Photonics Lett. Pol., 15(4), 54 (2023). CrossRef